2018
DOI: 10.1103/physrevb.97.035121
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of surface-state thermal oscillations in SmB6 oscillators

Abstract: SmB6 is a mixed valence Kondo insulator that exhibits a sharp increase in resistance following an activated behavior that levels off and saturates below 4K. This behavior can be explained by the proposal of SmB6 representing a new state of matter, a Topological Kondo insulator, in which a Kondo gap is developed and topologically protected surface conduction dominates low temeprarture transport. Exploiting its non-linear dynamics, a tunable SmB6 oscillator device was recently demonstrated, where a small DC curr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Reducing the thickness of the SmB 6 plate requires a smaller external capacitor until the device spontaneously starts oscillating with a frequency of the order of 10 7 Hz [88]. The behaviors of the oscillators agree well with a theoretical model describing the thermal Joule heating and electronic dynamics of coupled surface and bulk states [88,89]. An impedance study on SmB 6 single crystals, performed at low T and over a wide frequency range revealed the transition from surface to bulk dominated electrical conduction between 2 and 10 K [90].…”
Section: The Case Of Smb6supporting
confidence: 60%
“…Reducing the thickness of the SmB 6 plate requires a smaller external capacitor until the device spontaneously starts oscillating with a frequency of the order of 10 7 Hz [88]. The behaviors of the oscillators agree well with a theoretical model describing the thermal Joule heating and electronic dynamics of coupled surface and bulk states [88,89]. An impedance study on SmB 6 single crystals, performed at low T and over a wide frequency range revealed the transition from surface to bulk dominated electrical conduction between 2 and 10 K [90].…”
Section: The Case Of Smb6supporting
confidence: 60%
“…19 A model which involves both surface and bulk states, in addition to a strong coupling between the thermal and the electrical properties, has recently been put forward to explain this response. 20,21 Nevertheless, there are only few reports on the frequency-dependent transport properties of SmB 6 .…”
Section: Introductionmentioning
confidence: 99%
“…This ratio is about or less than 80 in the crystals of Refs. [16,17,24], whereas it is larger than 10 4 for SmB 6 we have studied. As a result, raising the sample temperature by 1 K in the former case (from a base temperature of 2 K) is sufficient to drive SmB 6 crystals into a bulk conduction regime but our samples must be heated at least 5 K in order to reach the same conduction regime.…”
Section: Nonlinear Negative Differential Resistancementioning
confidence: 58%